2022
DOI: 10.3390/bs12090330
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness as a Mediator between Psychological Suzhi and Prosocial Behavior in Chinese Adolescents

Abstract: Prosocial behavior contributes to the well-being of individuals as well as the harmonious development of society. This research aimed to reveal the mechanisms underlying the relationship between the psychological suzhi and prosocial behavior of Chinese adolescents with the consideration of time. A total of 477 adolescents (228 boys, 49.1%; Mage = 14.04 and SD = 1.77) from southwest China completed three questionnaires during waves 1 and 2. Results showed that psychological suzhi and forgiveness were positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Consistent with previous research, experiencing frequent childhood adversities (e.g., CPAN) could hinder adolescents’ cognitive, personality, and social development, thereby weakening their psychological suzhi levels [ 70 ]. Consequently, individuals with low levels of psychological suzhi tend to show more psychological stress and conflict, leading to an increased incidence of mental health problems and reduced engagement in prosocial behaviors [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research, experiencing frequent childhood adversities (e.g., CPAN) could hinder adolescents’ cognitive, personality, and social development, thereby weakening their psychological suzhi levels [ 70 ]. Consequently, individuals with low levels of psychological suzhi tend to show more psychological stress and conflict, leading to an increased incidence of mental health problems and reduced engagement in prosocial behaviors [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical developments suggest that forgiveness may be a type of coping strategy that contributes to protecting an individual against violence and harassment (negative outcomes) as well as promoting positive outcomes (Garthe & Guz, 2019). Forgiveness has been found to be associated with greater prosocial behavior in adolescents (Chen et al, 2022;García-Vázquez et al, 2020). Indeed, an experimental study by Karremans et al (2005) showed that forgiveness promotes generous giving behaviors.…”
Section: Virtues As Predictors Of Prosocial Behavior In Adolescentsmentioning
confidence: 99%
“…These components of life satisfaction are related to a positive individual psychological condition, good physical condition, and good interpersonal functioning (Busseri et al, 2012). Forgiveness refers to a type of positive emotion where one can actively forgive others and feel at ease with oneself (Chen et al, 2022). Among the top-down factors that contribute to life satisfaction, forgiveness has been widely explored (Lachmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%